Internal jugular and vertebral vein volume flow in patients with clinically isolated syndrome or mild multiple sclerosis and healthy controls: results from a prospective sonographer-blinded study. (September 2014) - Chambers, Brian; Chambers, Jayne; Churilov, Leonid; Cameron, Heather; Macdonell, Richard
Objectives & Methods: We evaluated internal jugular vein and vertebral vein volume flow using ultrasound, in patients with clinically isolated syndrome or mild multiple sclerosis and controls, to determine whether volume flow was different between the two groups. Results: In patients and controls, internal jugular vein volume flow increased from superior to inferior segments, consistent with recruitment from collateral veins. Internal jugular vein and vertebral vein volume flow were greater on the right in supine and sitting positions. Internal jugular vein volume flow was higher in the supine posture. Vertebral vein volume flow was higher in the sitting posture. Regression analyses of cube root transformed volume flow data, adjusted for supine/sitting, right/left and internal jugular vein/vertebral vein, revealed no significant difference in volume flow in patients compared to controls. Conclusions: Our findings further refute the concept of venous obstruction as a causal factor in the pathogenesis of multiple sclerosis. Control volume flow data may provide useful normative reference values.